Керування характеристиками термометричного матеріалу TiNiSn1-xGax - Крайовський, В. (Видавництво Львівської політехніки, 2016)
Досліджено енергетичні, кінетичні та магнітні характеристики термометричного матеріалу TiNiSn1-xGax у діапазонах:T = 80?1400 K, x=0.01?0.15 і напруженості магнітного поля H £ 10 кГс. Показано, що характеристики TiNiSn1-xGax чутливі до зміни температури і можуть бути основою для виготовлення чутливих елементів термоперетворювачів. The electron energy state, magnetic and transport characteristics of thermometric materials TiNiSn1- xGax were investigated in the 80?1400 K temperature range and at charge carriers concentration from x=0.01?0.15 and H £ 10 kGs. The material TiNiSn1-xGax is sensitive to the temperature change and could be used as the basis for the sensitive thermoelectric devices. We investigated the crystal structure, electron density of states (DOS) and the kinetic and energy characteristics of n-TiNiSn heavily doped with the Ga impurity. Samples were synthesized at the laboratory of the Institute of Physical Chemistry, Vienna University. The TiNiSn1-xGax crystal-lattice periods were determined by X-ray analysis with the use of the Full-prof software. We employed a data array obtained by the powder method using a Guinier-Huber image plate system. The chemical and phase compositions of the samples were determined using a Ziess Supra 55VP scanning electron microscope and an EMPA energy dispersive X-ray analyzer. The electronic structure was calculated by the Korringa–Kohn–Rostoker (KKR) technique in the coherent potential approximation (CPA) and local density approximation (LDA), as well as the full-potential linearized plane wave (FP-LAPW) method within density functional theory (DFT). In the calculations, we used experimental values of the lattice constant on a k grid 10 ? 10 ? 10 in size and the Moruzzi–Janak–Williams exchangecorrelation potential parametrization. The width of the contoured energy window was 16 eV. The number of energy values for DOS calculations was 1000. To predict the behavior of the Fermi level, band gap, and electrokinetic characteristics of n-TiNiSn heavily doped with the Ga impurity, the electron density distribution (DoS) was calculated. The calculated results pretending to be adequate to experimental studies should account for complete information on the semiconductor’s crystalline structure. To obtain more accurate results, we calculated the DoS for almost all possible cases of the mutual substitution of atoms at sites of the TiNiSn unit cell. Shows the result most consistent with experimental data. It was found that the disordered structure TiNiSn1-x-уGax, of the TiNiSn compound is most probable. We note that the same result was obtained from structural studies of TiNiSn. The partial (to 1 at %) substitution of Sn atoms with Ga atoms generates donor-type structural defects in the crystal, and the Fermi level is in the band gap which becomes narrower.. In this semiconductor model, the Fermi level is in the band gap which is εg ≈ 282 meV. The same question arises when analyzing the behavior of the dependences (x) and (x) in TiNiSn1-x-уGax. For example, the (x) variation in the concentration range 0.02 ≤ x ≤ 0.10 shows that the modulation amplitude of the continuous energy bands of TiNiSn1-x-уGax HDCSs increases. Indeed, the activation energies (x) increase from (x = 0.05) = 38.3 meV to (x) (x = 0.07) = 59.2 meV. As we already noted, such behavior is possible only when compensating electrons appear in the p-type semiconductor due to the ionization of donors whose appearance was not initially assumed. In TiNiSn1-x-уGax samples, x > 0.05, the decrease in (x) indicates a decrease in the modulation amplitude of the continuous energy bands, which is possible only when the degree of compensation of TiNiSn1-x-уGax decreases due to a decrease or termination of the generation of donor-type structural defects. Thus, the initial assumption that n-ZrNiSn doping with Ga atoms by substituting Ti atoms is accompanied by the generation of only donor-type structural defects in the crystal does not allow consistent explanation of the behavior of the energy characteristics of TiNiSn1-x-уGax HDCS. The variations in the activation energy of hopping conduction (x) and the modulation amplitude of the continuous energy bands (x) unambiguously prove the existence of a donor source in TiNiSn1-x-уGax. Further, we will identify the possible mechanism for the appearance of donors. The series of studies on the crystalline structure, energy spectrum, and electro-kinetic parameters of the n-TiNiSn intermetallic semiconductor heavily doped with the Ce impurity allowed determination of the variation in the degree of compensation of the semiconductor due to the generation of both structural defects of donor nature during the substitution of Sn atoms with Ga atoms and defects of donor nature during the partial substitution of Ni sites with Sn atoms. The mechanism of the degree of compensation of the semiconductor as the result of the crystal structure transformation during doping, leading to the generation of structural defects of donor nature was established. The results of the electronic structure calculation are in agreement with experimental data and the TiNiSn1-x-уGax semiconductor is a promising thermectric material. The results are discussed in the framework of the heavily doped and compensated semiconductor model by Shklovsky-Efros.
Keywords: електронна структура; електроопір; коефіцієнт термо-ерс; electronic structure; resistivity; thermo-power coefficient